2011
DOI: 10.1099/mic.0.044875-0
|View full text |Cite
|
Sign up to set email alerts
|

RpoE1, an extracytoplasmic function sigma factor, is a repressor of the flagellar system in Brucella melitensis

Abstract: RpoE1, an extracytoplasmic function sigma factor, is a repressor of the flagellar system in Brucella melitensis Unité de Recherche en Biologie Molé culaire (URBM), Faculté s Universitaires Notre-Dame de la Paix Namur (FUNDP), 61 rue de Bruxelles, B-5000 Namur, BelgiumThe genome of Brucella melitensis contains genes coding for the sigma factors RpoD, RpoN, RpoH1, RpoH2, RpoE1 and RpoE2. Previously published data show that B. melitensis is flagellated and that an rpoE1 mutant overexpresses the flagellar protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 25 publications
(42 reference statements)
3
21
0
Order By: Relevance
“…Our results clearly indicate that MucR of B. melitensis is also a repressor of flagellar-gene expression and likely acts upstream of FtcR, the flagellar master regulator orthologous to Rem (68) through which MucR of S. meliloti acts (21,67). In B. melitensis 16M, flagellargene expression is very tightly regulated, given that the QS regulator VjbR (27), the sigma factors rpoEI (76,77) and rpoH2 (76), and the cyclic-di-GMP phosphodiesterase BpdA (78) have already been shown to be involved in flagellar regulation. Here, we show that MucR is an additional actor within this complex regulatory network.…”
Section: Discussionmentioning
confidence: 80%
“…Our results clearly indicate that MucR of B. melitensis is also a repressor of flagellar-gene expression and likely acts upstream of FtcR, the flagellar master regulator orthologous to Rem (68) through which MucR of S. meliloti acts (21,67). In B. melitensis 16M, flagellargene expression is very tightly regulated, given that the QS regulator VjbR (27), the sigma factors rpoEI (76,77) and rpoH2 (76), and the cyclic-di-GMP phosphodiesterase BpdA (78) have already been shown to be involved in flagellar regulation. Here, we show that MucR is an additional actor within this complex regulatory network.…”
Section: Discussionmentioning
confidence: 80%
“…The function of these putative GSR genes in Brucella spp. was largely uncharacterized prior to this study, although it has been reported that a B. melitensis rpoE1 mutant negatively regulates flagellar biosynthesis (18) and is attenuated at 4 weeks postinfection in a mouse model (17). In this study, we have defined a functional role for the B. abortus GSR system in response to acute acid and oxidative stress in vitro and in control of chronic infection in mice (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that a Brucella melitensis 16M ⌬rpoE1 mutant is atten-uated in BALB/c mice at 4 weeks postinfection (17) and exhibits derepressed flagellar biogenesis (17,18). However, this rpoE1 mutant did not have a survival defect in a hydrogen peroxide disk diffusion assay (17).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Interestingly, FlbT from S. meliloti could also restore the production of flagellin while the C. cresentus FlbT could not, confirming an opposite role for these two FlbT proteins. In their companion paper (Ferooz et al, 2011b), these authors demonstrate that the alternative sigma factor RpoE1 represses the production of FlgE (hook protein) and FliC (flagellin) via activation of an unknown repressor, which in turn negatively regulates the expression of the master flagellar regulator FtcR, since expression of both flaF and flbT regulator genes was also found to be increased in the rpoE1 mutant. A model combining and summarizing the two findings is presented in Fig.…”
Section: Peculiarities Of the Regulation Of The Brucella Flagellummentioning
confidence: 99%